ANALISA REAKTOR BIOGAS CAMPURAN LIMBAH KOTORAN KAMBING DENGAN JERAMI DAN EM4 SISTEM MENETAP - Eswanto Eswanto; Ilmi Ilmi (University of Muhammadiyah Jakarta, 2018)
Biogas is a gas mixture produced by methanogenic bacteria that occurs in naturally decomposable materials under anaerobic conditions. Currently, alternativf energy is needed as a replacement source of energy derived from fossil and petroleum, therefore the utilization of waste into biogas is one solution that must be developed. The purpose of this research is to obtain the characteristics of the sedentary system reactor and biogas yield. In this study biogas testing of goat waste with rice straw mixture and EM4 to produce methane gas. The results showed that the gas capacity produced was 0.1675 m3 / s and the 0.0023 kg period, on the other hand the gas pressure obtained was 19.1 N / m2 with a temperature of 36 °C. While the time required for the formation of gas that is for 5 day after the introduction of raw material into biogas reactor settled system.